EAU/ESPU guidelines on the management of neurogenic bladder in children and adolescent, part II, operative management - Stein, Raimund; Bogaert, Guy; Dogan, Hasan S.; 't Hoen, Lisette A.; Kocvara, Radim; Nijman, Rien J. M.; Quaedackers, Josine; Rawashdeh, Yazan F.; Silay, Mesrur S.; Tekgul, Serdar; Radmayr, Christian (Neurourology and urodynamics, 2020)
Background - Treatment in children and adolescents with a neurogenic bladder is primarily conservative with the goal of preserving the upper urinary tract combined with a good reservoir function of the bladder.
First published: 03 December 2019
Gesehen am 26.01.2021